Association between schizophrenia and Toxoplasma gondii infection in Algeria. (September 2020) - Kezai, Amir Med; Lecoeur, Cécile; Hot, David; Bounechada, Mustapha; Alouani, Med Lamine; Marion, Sabrina
Highlights: T. gondii seropositivity is significantly associated with schizophrenia. Schizophrenia patients under 38 years of age display higher seroprevalence rate compared to controls of the same age range. The levels of anti- T. gondii antibodies are reduced in seropositive schizophrenia patients compared to seropositive controls. Schizophrenia is associated with family history of psychological problems and parent inbreeding. Abstract: Toxoplasmosis has been previously associated with an increased risk of having schizophrenia in several epidemiological studies. The aim of this prospective study was to examine for the first time a possible association between positive serology to Toxoplasma gondii ( T. gondii ) and schizophrenia in the Algerian population. Seventy patients affected by schizophrenia according to DSM-5 criteria and seventy healthy controls were enrolled in the study. We found a significant association between schizophrenia and the infection status with a seroprevalence of 70% in patients with schizophrenia compared to 52.9% in controls and a calculated odds ratio of 2.081. In addition, while T. gondii seroprevalence increases significantly with age in controls, this association was not observed in patients with schizophrenia, which display a high percentage of seropositive subjects under 38 years of age, suggesting that T. gondii infection may promote the onset of schizophrenia. Moreover, our analysis also revealed that patients with schizophrenia had significantly lower levels of serum immunoglobulins G (IgG) to T. gondii compared to controls. Thus, this study adds to previous research questioning the asymptomatic aspect of chronic toxoplasmosis and the etiology of schizophrenia.